2020
DOI: 10.1002/mnfr.202000576
|View full text |Cite
|
Sign up to set email alerts
|

S‐Allylcysteine Inhibits PhIP/DSS‐Induced Colon Carcinogenesis through Mitigating Inflammation, Targeting Keap1, and Modulating Microbiota Composition in Mice

Abstract: The objective of the present study is to investigate whether edible S-allylcysteine (SAC) has chemoprophylactic effects on inflammation-associated colon carcinogenesis induced in mice through 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) exposure and promoted by dextran sodium sulfate (DSS) and whether its cancer-prevention effects are related to the modulation of gut microbiota composition. Methods and results: Dietary administration of 0.05% SAC in mice for 18 weeks prevents shortening of the colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…These results suggested that SAC may mitigate PhIP-induced mutagenic effects by mediating the Nrf2 antioxidant signaling pathway at the initiation stage of colon cancer. [29] In the present study, we used CETSA experiments to provide evidence supporting the supposition that SAC could engage with Keap1 in normal human colonic mucosal epithelial cells. Furthermore, SAC inhibited p38 and increased AKT and ERK phosphorylation, consequently reinforcing Nrf2 signaling and upregulating HO-1 expression in NCM460 cells.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…These results suggested that SAC may mitigate PhIP-induced mutagenic effects by mediating the Nrf2 antioxidant signaling pathway at the initiation stage of colon cancer. [29] In the present study, we used CETSA experiments to provide evidence supporting the supposition that SAC could engage with Keap1 in normal human colonic mucosal epithelial cells. Furthermore, SAC inhibited p38 and increased AKT and ERK phosphorylation, consequently reinforcing Nrf2 signaling and upregulating HO-1 expression in NCM460 cells.…”
Section: Discussionmentioning
confidence: 65%
“…The amounts of SAC and PhIP used were based on previous studies. [28,29,54,55] NCM460 cells treated with 0.5% DMSO served as vehicle controls. The cells were seeded at a density of 2 × 10 5 cells mL −1 into 96-well plates and grown 12 h, the cells were treated either with or without PhIP (50 μM) in the presence and absence of SAC (5 or 20 mM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 IBD has been found to show an increasing incidence, which compromises healthy life and span, and increases the risk of colorectal cancer. 2 Crohn's Disease (CD) and Ulcerative Colitis (UC) are two major types of IBD that have been commonly diagnosed globally. 3 They have unique clinical, histopathological, radiological, and endoscopic characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), a relapsing and chronic intestinal inflammation that leads to the damage of gastrointestinal tract, usually causes weight loss, abdominal pain, persistent diarrhea, cramps, and rectal bleeding . IBD has been found to show an increasing incidence, which compromises healthy life and span, and increases the risk of colorectal cancer . Crohn’s Disease (CD) and Ulcerative Colitis (UC) are two major types of IBD that have been commonly diagnosed globally .…”
Section: Introductionmentioning
confidence: 99%